Primary Ewing's Sarcoma of Frontoparietal Bone with Major Soft Tissue Extension: An Unusual Presentation and Review of the Literature - Anshu Gupta; Sachin Bansal; Sujata Chaturvedi (Hindawi Limited, 2012)
An 11-year-old girl presented with progressively increasing swelling in scalp of 8-month duration with no neurological deficit. Local examination showed a hard swelling that seemed to be arising from frontal bone. General and systemic examination was normal. MRI revealed a well-defined lytic lesion in left frontoparietal bone with a subgaleal component. The patient was operated upon and excision of tumor with reconstruction of skull was done. Histopathological examination showed a monomorphic small round cell tumor of bone infiltrating into the subcutaneous tissue. Immunohistochemical stain showed diffuse immunopositivity for MIC-2 in tumor cells, thus final diagnosis of Ewing's sarcoma was made. The patient was kept for follow up for 3 months and had no symptoms.